Evaluation of hematological parameters of small ruminants affected by zoonoses at the municipal abattoir of Korhogo (Côte d’Ivoire) - Kamagate, Soualio; Ouedraogo, Mohamado; Dosso, Kassim; Yapo, Paul Angoué (Acta Scientiarum. Biological Sciences, 2025)
This study was conducted to highlight the effect of zoonotic diseases on the hematological parameters of small ruminants from the municipal abattoir of Korhogo. A total of 170 small ruminants, comprising 85 sheep and 85 goats, some of which were detected with zoonotic diseases, were recruited for blood analysis. Blood samples were collected from the jugular vein using EDTA anticoagulant tubes. Complete Blood Count (CBC) was performed on these blood samples. The main results indicate that 34.71% of the small ruminants were sick, with 38.82% among sheep and 30.58% among goats. Tuberculosis was detected in 20.59% of the total population, compared to 14.12% with fascioliasis. Comparison of hematological parameters between healthy and sick animals revealed that blood parameters were more altered in sick animals than in healthy ones. Anemia was the most observed hematological complication in sick animals, with average hemoglobin levels of 7.77 ± 0.39 g L-1 in sick sheep and 7.42 ± 0.49 g L-1 in sick goats. Statistical analysis showed a significant correlation between hemoglobin levels and zoonotic pathology in both sheep and goats, with coefficients of 0.261 and 0.254, respectively. These results suggest that zoonotic pathologies are responsible for hematological complications especially anemia in small ruminants slaughtered at the municipal abattoir in Korhogo. These diseases should thus be detected through blood tests before slaughter to preserve their health and provide high-quality meat to the population.